Optical characterization of a funnel solar cooker with azimuthal sun tracking through ray-tracing simulation - Carrillo-Andrés, Antonio; Apaolaza-Pagoaga, Xabier; Rodrigues-Ruivo, Celestino; Rodríguez-García, Eduardo Amador; Fernández-Hernández, Francisco Ángel (Elsevier, 2022)
Funnel type solar cookers are simple and effective. Most of them rely on a multifaceted reflector to concentrate solar radiation on a cooking pot that is placed inside a transparent enclosure to create a greenhouse effect. The analysis of the resulting optical system is a complex task, as multiple reflections occur. The overall performance of funnel solar cookers is strongly affected by their optical efficiency. There is a lack of information in academic literature about this important research topic. This work aims to fill this gap presenting an optical performance analysis of a funnel solar cooker with only azimuthal sun tracking. Open-source numerical ray-tracing software Soltrace is used to investigate relevant characteristics such as the intercept factor, optical efficiency, dependency on incidence angle, performance of each reflecting surface and irradiation density flux distribution on different surfaces of the cooking pot. Some important results for beam radiation at normal incidence are the intercept factor, determined to be 0.664, and the optical efficiency with realistic optical properties, that turned out to be 0.370. When the incidence of solar beam radiation is not normal, optical efficiency remains above 90% of its normal incidence value, if the alignment errors are less than 10◦.
Keywords: Energía solar - Aplicaciones; Solar energy; Solar cooker; Funnel cooker; Ray-tracing; Soltrace